2006
DOI: 10.1103/physrevlett.97.070402
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tension in Unitary Fermi Gases with Population Imbalance

Abstract: We study the effects of surface tension between normal and superfluid regions of a trapped Fermi gas at unitarity. We find that surface tension causes notable distortions in the shape of large aspect ratio clouds. Including these distortions in our theories resolves many of the apparent discrepancies among different experiments and between theory and experiments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 44 publications
4
104
0
Order By: Relevance
“…Also at Rice University a further study was performed, where Partridge et al observed a deformation of the superfluid core at their lowest temperatures [71]. This deformation was explained in terms of a first-order interface between the superfluid core and the normal outer region in the trap [144,149], see also Fig. 8(c).…”
Section: Experimental Overviewmentioning
confidence: 92%
See 2 more Smart Citations
“…Also at Rice University a further study was performed, where Partridge et al observed a deformation of the superfluid core at their lowest temperatures [71]. This deformation was explained in terms of a first-order interface between the superfluid core and the normal outer region in the trap [144,149], see also Fig. 8(c).…”
Section: Experimental Overviewmentioning
confidence: 92%
“…4), where the atom number in each of the two states could be precisely tuned. Within a few months time these experiments were followed by a large amount of theoretical studies, which studied the imbalanced Fermi gas using mean-field approaches [100,135,136,137,138,85], using thermodynamic approaches [139,140], using diagrammatic approaches [141], using the Bogoliubov-de Gennes approach [142,143], including the effects of surface tension [144], including the gradient energy of the density profiles [145], and including Gaussian order parameter fluctuations [146]. The interesting aspect of a polarization in the system is that not all atoms can find a partner to pair up with, because the fermions only have attractive s-wave interactions when they are in different hyperfine states.…”
Section: Experimental Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The non monotonic structure of the density observed in the Rice experiment can be explained through the inclusion of surface tension effects. For a recent discussion of surface tension and thermal effects in spin imbalanced configurations see De Silva and Mueller (2006b), Partridge et al (2006b) and Haque and Stoof (2007).…”
Section: Phase Separation In Harmonic Traps At Unitaritymentioning
confidence: 99%
“…Such a phase-separation scenario had been proposed by Clogston [27] and Chandrasekhar [28] long ago, who predicted the occurrence of a first-order transition from the N to the SF state. Since the existence of a N-SF interface may settle some important questions regarding polarized Fermi mixtures, serious research has been focused on this subject [29][30][31]33]. In particular, it has been established [30,31] that a temperature difference between the two phases can appear as a consequence of the blockage of energy transfer across the N-SF interface.…”
Section: Introductionmentioning
confidence: 99%